Differences in reading and mathematics skills in relation to educational quality in Peruvian students at the primary education level - Canales Gabriel, Ricardo (2025)
This study aimed to examine the potential relationship between competencies and learning outcomes in reading and mathematics among children attending public schools, and the different levels of educational quality, using official data from the Ministry of Education of Peru.Using previously designed psychopedagogical tests, reading and mathematics competencies were assessed in 217 third-grade students from schools in Callao. The students were grouped based on whether their schools had received the “school bonus” awarded by the Ministry of Education (MINEDU) in 2016 and 2017, or had not received it. Significant differences were found in the assessed domains of reading and mathematics, in favor of students attending schools that had received the bonus. In reading, these differences were evident in the various psychological processes involved: phonological, lexical, syntactic, and semantic. In mathematics, differences were found in number writing, but not in simple calculation operations or problem solving.The study discusses whether complex cognitive processes and basic learning outcomes are linked to the educational processes that take place in institutions characterized by certain levels of educational quality.